Prevalence and trend of TB/HIV co-infection in Suhum Municipality, Ghana - Haruna M. Salisu; Inumanye N. Ojule; Foluke O. Adeniji; George K. Kwakye (Public Library of Science (PLoS), 2022)
Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) infections have been identified to form a deadly synergy that is posing serious threats to human health and economic development particularly in Sub-Saharan Africa (SSA). Six years into the end TB strategy, it is imperative to assess HIV detection rate among TB patients in order to determine the prevalence as well as establish the temporal trend of the co-morbidity in the Eastern region of Ghana where the magnitude of HIV and TB/HIV co-morbidity have consistently been noted to be high. The study reviewed records of 840 TB patients retrospectively from January 1, 2009 to December 31, 2018 in Suhum Municipal. Socio-demographic characteristics and clinical data of study participants were extracted from the Municipal TB registers using an excel spread sheet. Data were exported into STATA version 16.0 for analysis with statistical significance set at p-value ≤0.05. Of the 840 TB patients, 793 (94.4%) were screened for HIV, with 18.6% (95% CI: 0.16-0.21) yielding positive results. A sharp increase in the trend of the co-infection was observed from 6 (14.6%) in 2009 to 21 (36.8%) in 2010. The highest (40.4%) co-infection prevalence was recorded in 2011. The study recorded an overall decreasing trend of the co-infection. Case detection rate for HIV among persons living with TB was high. TB/HIV co-infection rate in Suhum Municipal is high and occurs more often among females and persons aged 30 years to 49 years. A fairly stable prevalence trend of TB/HIV co-infection rate was also identified. In conclusion, ongoing integrated TB/HIV activities are showing good results and therefore need to be sustained.